The financial toxicity of ageing: a longitudinal analysis of the health and functional determinants of household OOP spending in rural South Africa - Ugwu, Lawrence Ejike; White, Janine Anthea; Aplin-Houtz, Matthew; Idemudia, Erhabor Sunday (Frontiers in Public Health, 2026)
BackgroundIn sub-Saharan Africa, the epidemiological transition has created a double burden of chronic disease and functional decline. While the relationship between non-communicable diseases (NCDs) and out-of-pocket (OOP) health expenditure is well-established, less is known about the financial burden of physical frailty and cognitive decline. This study investigates the “financial toxicity” of ageing, distinguishing between the costs of disease diagnosis and those of functional disability.MethodsWe analysed longitudinal data from the Health and Ageing in Africa: A Longitudinal Study (HAALSI) in rural South Africa (Waves 1–3, 2015–2022). The analytic sample included 4,371 adults aged ≥40 years (13,437 person-wave observations). We utilised Generalised Estimating Equations (GEE) to model two outcomes: the likelihood of incurring any OOP health expenditure (market entry) and the magnitude of spending among payers (financial toxicity). Predictors included chronic diagnoses (hypertension, diabetes, HIV), objective function (grip strength, gait speed), and cognitive/mental status (delayed recall, depression), adjusting for sociodemographic factors.FindingsSocioeconomic status and NCD diagnoses were the primary drivers of market entry; hypertension was associated with a 26% increase in spending (AOR 1.26, 95% CI 1.14–1.40). Among those incurring costs, physical frailty (weaker grip strength) was associated with a greater magnitude of spending (p = 0.012). However, severe vulnerability unexpectedly predicted lower spending: for every additional Activity of Daily Living (ADL) limitation, the odds of incurring costs decreased by 16% (AOR 0.84, p < 0.001), and depression was associated with significantly lower expenditure intensity (p < 0.001). HIV-positive status was protective against high OOP costs.ConclusionThe financial toxicity of ageing is characterised by a “dual burden of exclusion.” While NCD diagnoses drive households into the payment system, severe functional and mental decline appears to act as a barrier to access, effectively excluding the most vulnerable from the formal health economy. Financial risk protection mechanisms must be expanded beyond disease-specific models to cover geriatric frailty and disability explicitly.